Analysis of the revolving vane (RV-0) expander, part 2 : verifications of theoretical models - Subiantoro, Alison (2013)
Various aspects of the Revolving Vane (RV-0) expander have been theoretically modelled. They include the geometry, kinematics, dynamics, thermodynamics, flow through ports and internal leakage aspects. The models have also been compared to the experimental data. It was found that the predicted output torque matches with the experimental data with an average deviation of 20% while the flow rate predictions have an average deviation of 25%. The temperature of the journal bearing lubricant and the leakage flow rate through the housing clearances are thought to be the main sources of discrepancies. The study also found that the main contributor of the internal leakage is the flow through the radial clearance.